Analysis of SEO Strategy and Interactive Content Marketing in Increasing Online Visibility and Sales at E-Commerce in West Java - Faridah, Faridah; Nugroho, Budi; Arini, Rani Eka (Westscience Press, 2025)
This study investigates the impact of SEO Strategy and Interactive Content Marketing on online visibility and sales in the e-commerce sector in West Java. A quantitative research design was employed, with data collected from 190 respondents using a Likert scale (1–5). Data analysis was conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS). Results reveal that Interactive Content Marketing significantly improves online visibility and sales, while SEO Strategy also contributes positively, albeit to a lesser degree. Online visibility plays a crucial role in driving sales. The study highlights the synergistic relationship between SEO and interactive content in enhancing e-commerce performance. These findings offer valuable insights for practitioners seeking to optimize digital marketing strategies in competitive online markets.